2021
DOI: 10.1021/jacs.1c01831
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Moisture-Responsive Crystalline Smart Materials for Water Harvesting and Electricity Transduction

Abstract: It is of profound significance with regard to the global energy crisis to develop new techniques and materials that can convert the chemical potential of water into other forms of energy, especially electricity. To address this challenge, we built a new type of energy transduction pathway (humidity gradients → mechanical work → electrical power) using moisture-responsive crystalline materials as the media for energy transduction. Single-crystal data revealed that a flexible zeolitic pyrimidine framework materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
47
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(49 citation statements)
references
References 54 publications
1
47
0
1
Order By: Relevance
“…Recent demonstrations and theoretical predictions showed that such WR actuation could be extremely powerful and efficient, [7][8][9] inspiring the growing studies and development of WR structures for actuators and artificial muscles. [10][11][12][13][14][15][16][17] Notable WR examples include a titanium oxide film [18] and a twisted carbon nanotube yarn, [19] which exhibit WR energy densities of ≈1250 and 1800 kJ m −3 (2.17 kJ kg −1 ), respectively. Microrobots equipped with WR actuators of 𝜋-stacked carbon nitride films [8] and polyethylene oxide nanofibers [20] have been demonstrated to exhibit autonomous locomotion powered by fluctuations in ambient RH.…”
Section: Doi: 101002/advs202104697mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent demonstrations and theoretical predictions showed that such WR actuation could be extremely powerful and efficient, [7][8][9] inspiring the growing studies and development of WR structures for actuators and artificial muscles. [10][11][12][13][14][15][16][17] Notable WR examples include a titanium oxide film [18] and a twisted carbon nanotube yarn, [19] which exhibit WR energy densities of ≈1250 and 1800 kJ m −3 (2.17 kJ kg −1 ), respectively. Microrobots equipped with WR actuators of 𝜋-stacked carbon nitride films [8] and polyethylene oxide nanofibers [20] have been demonstrated to exhibit autonomous locomotion powered by fluctuations in ambient RH.…”
Section: Doi: 101002/advs202104697mentioning
confidence: 99%
“…Recent demonstrations and theoretical predictions showed that such WR actuation could be extremely powerful and efficient, [ 7 , 8 , 9 ] inspiring the growing studies and development of WR structures for actuators and artificial muscles. [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 ]…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, smart materials have been studied extensively for their important applications in molecular switches, white light-emitting diodes, information storage, , anti-counterfeiting, , separation and detection, drug delivery, , and other fields. Smart material molecules can reversibly change their physical and chemical properties under different external stimuli. , Among various external stimuli, including light energy, electrical energy, and chemical energy, light is the most suitable and convenient source of clean energy and has advantages of precise control as a stimulus source and energy-saving and environmental protection characteristics. Previously reported light stimulation of smart molecules includes the trans-to-cis isomerization of azobenzene and stilbene derivatives, photocyclization of diarylethylenes, [2 + 2] cycloaddition of alkenes, and [4 + 4] photodimerization of anthracene. Photoinduced trans-to-cis isomerization has attracted much attention in inorganic and organic chemistry, materials science, and biology.…”
Section: Introductionmentioning
confidence: 99%
“…There are only a handful of piezoelectric actuators that can convert the chemical potential in humidity to pulse electricity in low efficiency. , However, the electricity generated is too weak to enable the sensing capability and communicating with external electrics unless applying rectifier circuits. The recent technology of moist-electric generation (MEG) provides the feasibility of generating electricity with high voltage from humidity by ionic diffusion in hydrophilic materials. ,,, Applying this concept to moisture-responsive soft actuators is promising in realizing not only electricity generation but also self-powered sensing of their actuating patterns and humidity, which, however, remains unexplored by far.…”
mentioning
confidence: 99%
“…It is the only humidity-responsive actuator that can simultaneously harvest the humidity energy to mechanical power and electricity for enabling self-powered sensing of humidity and motion modes in real-time (Figure , Table S1). , , Such multiple functionalities are integrated into a polyethylene terephthalate (PET)-supported composite membrane (MCPM) of MXene, cellulose, and polystyrene sulfonic acid (PSSA) by directional proton diffusion and asymmetric expansion under moisture gradient (Figure a). The obtained soft actuator exhibits a maximum bending angle of 130 o , while generating the electricity with a maximum power density of 81.2 μW cm –3 and an open-circuit voltage ( V OC ) of 0.3 V. With these benefits, it can be used for developing not only power sources but also self-powered smart switches, soft robots, human-touching, and breathing monitors with high sensitivity.…”
mentioning
confidence: 99%